2013
DOI: 10.1016/j.celrep.2013.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effect of EGFRWT on EGFRvIII-Mediated NF-κB Activation with RIP1 as a Cell Death Switch

Abstract: Summary RIP1 is a central mediator of cell death in cell stress, but can also mediate cell survival by activating NF-κB. Here, we show that RIP1 is a switch in EGFR signaling. EGFRvIII is an oncogenic mutant that does not bind ligand and is co-expressed with EGFRwt in glioblastoma (GBM). EGFRvIII recruits ubiquitin ligases to RIP1 resulting in K63-linked ubiquitination of RIP1. RIP1 binds to TAK1 and NEMO forming a EGFRvIII-RIP1 signalosome that activates NF-κB. RIP1 is essential for EGFRvIII-mediated oncogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 41 publications
2
47
1
Order By: Relevance
“…Although it is currently unclear whether this pathway is specifically induced in glioma cells resistant to EGFR inhibitors, this study nevertheless shows that NF-kB also acts as a central player in chemotherapy resistance in glioblastoma cells harboring constitutivelyactive EGFR. EGFRvIII also activates NF-kB in glioma cells by assembling a signaling platform with TNF receptor-associated protein 2 (TRAF2), RIPK1, both the cIAP1 and cIAP2 (cellular inhibitor of apoptosis 1/2) E3 ligases, as well as TAK1 [56]. RIPK1 becomes polyubiquitinated in a K63-linked, non-degradative manner to trigger TAK1 and subsequent IKKb phosphorylation.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is currently unclear whether this pathway is specifically induced in glioma cells resistant to EGFR inhibitors, this study nevertheless shows that NF-kB also acts as a central player in chemotherapy resistance in glioblastoma cells harboring constitutivelyactive EGFR. EGFRvIII also activates NF-kB in glioma cells by assembling a signaling platform with TNF receptor-associated protein 2 (TRAF2), RIPK1, both the cIAP1 and cIAP2 (cellular inhibitor of apoptosis 1/2) E3 ligases, as well as TAK1 [56]. RIPK1 becomes polyubiquitinated in a K63-linked, non-degradative manner to trigger TAK1 and subsequent IKKb phosphorylation.…”
Section: Reviewmentioning
confidence: 99%
“…EGFRvIII expression also promotes cell survival in glioma cells through K63-linked polyubiquitination of RIPK1 by c-IAPs bound to TRAF2. This signaling complex culminates in NF-kB activation through TAK1-dependent IKKb phosphorylation [56]. atypical protein kinase C (aPKC) bound to the scaffold protein p62 to induce the expression of proinflammatory cytokines through NF-kB.…”
Section: Reviewmentioning
confidence: 99%
“…Specifically, NF-κB is activated by epidermal growth factor (EGF), and/or its receptor, (EGFR), the latter of which is frequently mutated and constitutively activated [3638]. Moreover, it has been shown that oncogenic EGFR activates NF-κB by way of mTORC2, and this signaling cascade promotes chemoresistance [39].…”
Section: Nf-κb In Gbmmentioning
confidence: 99%
“…However, recent studies suggest that EGFRwt is usually co-expressed in EGFRvIII expressing tumor cells. Fan et al, showed the co-localization of EGFRwt and EGFRvIII in individual tumor cells by immunohistochemistry in GBM samples with antibodies specific for EGFR and EGFRvIII (23), while Puliyapaddamba et al, showed that clones derived from single cells from primary GBM cultures expressed both EGFRwt and EGFRvIII (24). The co-expression of both EGFRwt and EGFRvIII within the same tumor raises the possibility of interactions between the receptors and a number of studies have investigated EGFRwt-EGFRvIII interactions as outlined below.…”
mentioning
confidence: 99%